VULKANOSTRATIGRAPHY AND PETROGENESIS OF THE SADAKELING - KARAHA COMPLEX REGION , TASIKMALAYA REGENCY, WEST JAVA - Ezziat Putera Muhammad, Azrie
The Sadakeling-Karaha Volcano Complex is a type-C volcano located between Tasikmalaya and Garut, West Java Province. Apart from not being precisely mapped, previous studies only discussed the geothermal system of Karaha Crater. Based on its tectonics, this area can be a continuous fragment of the Australian Continent Argoland, which is one of the controls in the magmatism process. This study aims to map the volcanostratigraphy, the history of the formation and evolution of magma, and determine the tectonic setting and continuity of Argoland, based on the study of petrogenesis. The data used is in rock samples by observing rock texture and plagioclase microtexture and geochemistry. Based on the volcanostratigraphy analysis, the Sadakeling - Karaha complex consists of 4 Khuluks and 12 Volcanic Gumuks formed during 7 phases. The Sadakeling – Karaha complex has fairly complex magma evolution characteristics characterized by repeated differentiation, magma assimilation, and primitif magma injection as reflected by fluctuations in anorthite content, texture in each lava unit, and Harker diagrams between major oxide compounds and silica. More specifically, the evolution of magma that occurs can be reflected from the plagioclase microtexture, which includes the crystal fractionation process, the decompression process due to primitif magma, the self-mixing process due to convection, heating due to primitif magma mixing, cooling due to eruption, and decompression process during the eruption. Analysis of spider diagrams, bivariat and triangular diagrams between geochemical content, as well as comparisons between trace elements, show that in tectonic aspect, Sadakeling - Karaha Complex is part of a volcanic arc that is influenced by subduction processes and crustal contamination so that it is included in the active continental margin with magma series is tholeiitic – alkaline calc. Based on data from the content of Sr, Nd, and their comparisons, it is shown that there is an influence of contamination